Diagnosis and Management of Hoarseness in Developing Country - Aremu, Shuaib Kayode; Adegbiji, Waheed Atilade; Nwawolo, Clement; Olajuyin, Oyebanji Anthony; Olatoke, Fatai (Open Science Journal, 2018)
Background: Hoarseness/dysphonia of voice is the most common symptom of laryngeal disorder regardless of its pathology. This study aimed at determining the sociodemographic profile, aetiology, predisposing factors, clinical profile and management of hoarseness. Materials and Methods: This study was a prospective study carried out on all patients who presented hoarseness of voice via the Ear, Nose, and the Throat at the department of a tertiary institution in Nigeria. The study was carried out between October 2015 to September 2017. Data were obtained from patients who gave consent by using pre tested interviewer assisted questionnaire. All the data obtained were analyzed using SPSS version 16.0. Results: Prevalence of hoarseness was 2.4%. There were 58.4% males with male to female ratio being 1.5:1. Housewives were involved 27.6%, Singers 21.5%, Teachers 17.3%, and Clergy 13.1%. Main causes were 96.3% organic causes and 2.8% neurological causes. Common organic causes were 36.4% acute laryngitis, 30.8% chronic laryngitis, and 15.0% vocal nodules. Main predisposing factors were Upper respiratory tract infections 50.5%, Voice abuse 33.6%, and Laryngopharyngeal reflux 29.4%. Commonest duration of the hoarseness prior to presentation were >12 months in 29.4% and 6–9 months in 27.1%. Main clinical features were hoarseness 78.5%, catarrh/cold 73.4%, sensation of lump in the throat 62.6%, and cough 55.6%. Prior medications before presentation to otorhinolaryngologist were local herb 84.6%, over the counter medication 48.6%, and health care center 38.3%. Specialist care was conservative/medical treatment 77.6%, surgical intervention 20.1%, and referral 2.3%. Conclusion: Prevalence of hoarseness of voice was high with associated presentation to the specialist. Organic causes are the commonest with predominant inflammatory origin. Laryngeal neoplasm with associated malignancy was significant in a numbers of patients.